Long non‐coding RNA GAS5 is induced by interferons and plays an antitumor role in esophageal squamous cell carcinoma. (9th May 2018) - Huang, Jianbing; Li, Yuan; Lu, Zhiliang; Che, Yun; Sun, Shouguo; Mao, Shuangshuang; Lei, Yuanyuan; Zang, Ruochuan; Li, Ning; Sun, Nan; He, Jie
Abstract: The long non‐coding RNA GAS5 has been reported as a tumor suppressor in many cancers. However, its functions and mechanisms remain largely unknown in esophageal squamous cell carcinoma (ESCC). In this study, we found that GAS5 was over‐expressed in ESCC tissue compared with that in normal esophageal tissue in a public database. Functional studies showed that GAS5 could inhibit ESCC cell proliferation, migration and invasion in vitro. Further analysis revealed that GAS5 was regulated by interferon (IFN) responses via the JAK‐STAT pathway. Moreover, as an IFN‐stimulated gene (ISG), GAS5 was a positive regulator of IFN responses. The feedback loop between GAS5 and the IFN signaling pathway plays an important antitumor role in ESCC, thus providing novel potential therapeutic targets. Abstract : In this study, we found that long non‐coding RNA GAS5 was transcription activated by interferons via JAK‐STAT pathway, and could inhibit cancer cell proliferation, migration, and invasion in esophageal squamous cell carcinoma (ESCC). What's more, GAS5 was a positive regulator of interferon responses. The feedback loop between GAS5 and the IFN signaling pathway plays an important antitumor role in ESCC, thus providing novel potential therapeutic targets.